Experimental study on mechanical and acoustic emission characteristics of sedimentary sandstone under different loading rates - Li, Nianchun; Feng, Quanlin; Yue, Weijia; Sun, Shuhai; Li, Yantao; Li, Gaoyuan; Shi, Wei (Frontiers in Earth Science, 2023)
In the field of rock engineering, complexity of stress environment is an important factor affecting its stability. Thus, in view of fracture mechanism of rock under different loading rates within the scope of quasi-static strain rate, four groups of uniaxial compression tests with different strain rates were carried out on sandstone specimens, and strength, deformation, failure modes and acoustic emission characteristics of specimens were compared and analyzed. Furthermore, the fracture mechanism was discussed from the perspective of fracture characteristics based on fractal dimension, crack propagation law inverted through acoustic emission b-value, and micro fracture morphology. The results showed that as the strain rate increased from 10-5 s-1 to 10-2 s-1, the fractal dimension of rock fragments increased, and the fractal dimension of rock fragments increased by 9.66%, 7.32% and 3.77% successively for every 10 times increase in strain rate, which means that the equivalent size of fragments was getting smaller, and the fragmentation feature was becoming increasingly prominent. The crack propagation process based on acoustic emission b-value showed that with the increase of loading rate, the specimen entered the rapid crack propagation stage earlier, in order of 68%, 66%, 29% and 22% of peak stress. Moreover, the microscopic fracture morphology showed that with the increase of loading rate, transgranular phenomenon was clear, and the fracture morphology changed from smooth to rough. That meant that the fracture of sandstone rock at high loading rates was mainly caused by the propagation of large cracks, which was different from the slow process of initiation, convergence and re-propagation of small cracks at low strain rates.